VKORC1 and CYP2C9 polymorphisms related to adverse events in case-control cohort of anticoagulated patients. Issue 52 (December 2016) - Misasi, Silvia; Martini, Giuliana; Paoletti, Oriana; Calza, Stefano; Scovoli, Giovanni; Marengoni, Alessandra; Testa, Sophie; Caimi, Luigi; Marchina, Eleonora
Abstract : Abstract: Vitamin K antagonists (VKAs) are highly effective but have a narrow therapeutic index and require routine monitoring of the INR. The primary aim of pharmacogenetics (PGx) is to optimize patient care, achieving drug treatments that are personalized according to the genetic profile of each patient. The best-characterized genes involved in VKA PGx involve pharmacokinetics ( VKORC1 ) and pharmacodynamics ( CYP2C9 ) of VKA metabolism. The role of these genes in clinical outcomes (bleeding and thrombosis) during oral anticoagulant (OAC) therapy is controversial. The aim of the present study was to evaluate any potential association between genotype VKORC1 and CYP2C9 and adverse events (hemorrhagic and/or thrombotic), during initiation and long-term VKA treatment, in Caucasian patients. Furthermore, we aimed to determine if the concomitant prescription of other selected drugs affected the association between genotype and adverse events. We performed a retrospective, matched case-control study to determine associations between multiple gene variants, drug intake, and any major adverse effects in anticoagulated patients, monitored in 2 Italian anticoagulation clinics. Our results show that anticoagulated patients have a high risk of adverse events if they are carriers of 1 or more genetic polymorphisms in the VKORC1 (rs9923231) and CYP2C9 (rs1799853 and rs1057910) genes. Information on CYP2C9 and VKORC1 variants may be useful to identify individualized oral anticoagulant treatment for each patient, improve management and quality of VKA anticoagulation control, and monitor drug surveillance in pharmacovigilance programs.